STRATEGI KEPALA MADRASAH DALAM PEMBERDAYAAN KOMITE UNTUK MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH TSANAWIYAH SWASTA YAYASAN MADRASAH PENDIDIKAN ISLAM SEI TUALANG RASO KOTA TANJUNGBALAI - Nursam Damanik, Siti; Nahar, Syamsu; Budianti, Yusnaili (JURNAL TARBIYAH, 2023)
This study aims to describe the strategy of the madrasah principal in empowering the community to improve the quality of the madrasah, the role and cooperation of the madrasah principal with the committee in improving the quality of education and the empowerment of the Madrasah Committee in improving the quality of education at the Private Junior High School of the Sei Islamic Education Foundation. Tualang Raso, Tanjungbalai City. The method used in this study is a qualitative method. The technique used in analyzing the data is to record data from interviews and observations. The findings of the study illustrate that the empowerment of the madrasah committee, especially in relation to improving the quality of madrasah education, has not taken place as expected, the empowerment efforts are only temporary, and the cooperative relationship between the madrasah principal and the committee is going well, meaning that there are no problems that arise so that both have a harmonious relationship and the School Committee is an independent body and does not have a hierarchical relationship with schools or other government institutions. Supporting factors in efforts to empower the madrasah committee in improving the quality of education are carried out by the madrasah principal by maximizing the functions and duties of the committee at school.